PERANCANGAN ENCLOSURE UNTUK MEREDUKSI KEBISINGAN DI UNIT STEAM TURBINE BLOK I – PLTGU PT. X - Admin APERTI (JURNAL TEKNOLOGIA, 2018)
The steam turbine is one of the components in combined steam and gas power plant PT. X which serves to expand the vapor to produce mechanical energy to drive the generator. In operation, steam turbine can pose a danger to humans, one of which is noise. Noise is the emergence of unwanted sounds that may interfere with or endanger health. Based on the decision of the Minister of Manpower, Transmigration and Cooperatives No. 51 / Men / 1999, noise threshold of 85 dB(A) per 8 hours per day. If exposure to noise exceeds the noise threshold continuously, it may cause disruption to nearby workers. Therefore, research will be conducted to control the noise level by designing the enclosure in the steam turbine block I - PLTGU PT. X. Based on the measurement results that have been done,, the highest noise level on each floor is 93.6 dB (A) for the 1st floor, 90.7 dB (A) for the 2nd floor, and 93.2 dB (A) for the 3rd floor in the overall frequency. Based on the noise level after the enclosure design, the material suitable for the enclosure design in the steam turbine unit Block I - PLTGU is an aluminum sheet with a thickness of 1 mm. The addition and design of the enclosure can reduce the noise level by ± 25.8 dB (A).